Managerial Decision Support Making in Economic Systems Based on Cognitive Modeling - Filipkovska, L.; Matviienko, O. (International Journal of Engineering and Technology, 2018)
The research is devoted to the search for the technologies to support managerial decisions in the transport industry economic systems. The problems of the complex economic systems modelling have been identified. Cognitive modelling is considered as a tool of supporting intelligent decision making in economic systems. The modelling is based on methods of pattern recognition theory. The results of the scientific research are presented with structural-analytical models of decision support systems. Such models represent the knowledge processing to formulate recommendations for making managerial decisions. Knowledge based on the experience of managing a production situation should be stored in the knowledge base of the information decision making support system. Cognitive modeling will make it possible to study the problems that arise in unstable, weakly structured dynamic economic systems, taking into account changes of the external environment and the object of management itself, systematizing and verifying the expert's perception of the management object and its external environment, forecasting the values of economic system factors and generating optimal management strategies.Â Â